Am I treated better than my co-worker? A moderated mediation analysis of psychological contract fulfillment, organizational identification, and voice. Issue 5 (21st June 2018) - Ali Arain, Ghulam; Bukhari, Sehrish; Hameed, Imran; Lacaze, Delphine M.; Bukhari, Zahara
Abstract : Purpose: The purpose of this paper is to examine the direct and conditional indirect effects of employees' perception of psychological contract fulfillment on their positive voice, i.e., promotive voice and prohibitive voice, through the integrated framework of the social exchange theory and the group value model. Design/methodology/approach: Using a two-source data collection from the employee and supervisor, cross-sectional data were collected from 234 participants working in one of the leading non-profit organizations in Pakistan. After initial data screening, a confirmatory factor analysis was conducted to test for the factorial validity of the employed measures with AMOS. The hypothesized relationships were tested in regression analysis with Statistical Package for the Social Sciences. Findings: The results of this study supported the integration of the social exchange theory with the group value model in explaining the direct and indirect positive effects of employees' perception of psychological contract fulfillment on their promotive and prohibitive voices through the mediation of organizational identification (OID). Furthermore, it was also recorded that the indirect effect was conditional on the employees' perception of the relative psychological contract fulfillment which significantly moderated the direct relationship between psychological contract fulfillment and OID. However, no such effect was recorded for the moderating effect of power distance orientation between OID and the both voices. Originality/value: In addressing the recently published research calls, this study broadens the horizon of existing research on psychological contract and employee positive voice by investigating the mediating and the moderating factors that influence this relationship.